Developing musicianship through performance in schola: Gregorian chant as the blueprint for musicality - Phillips O'Neil, Trenton (My University, 2025)
This report identifies the regular practice of Gregorian chant as a key factor in developing singers’ musicianship, particularly through energized breathing, ensemble awareness of vowel uniformity, and a collective sense of forward motion in the phrasing. In my work with choral ensembles, I often encountered frustration when students produced a weak tone and demonstrated inconsistent intonation – issues I initially attributed to a lack of note accuracy. The typical response involved repetitively plunking out individual parts, yet this yielded little improvement in overall musicality. Upon further reflection, I hypothesized that if students developed a deeper understanding of ensemble singing – specifically in tone production, blend, and intonation – their pitch and rhythmic accuracy would also improve. Teaching in a Catholic school provided a unique opportunity: each music class began with prayer, typically one of the seasonal Marian antiphons. I observed that my choir often sounded its best while chanting these prayers, even before formal warm-ups. The consistent use of monophonic melodies and free rhythms simplified the singing experience for less-trained voices, eliminating the challenges of dense harmonic textures and complex rhythmic notation. This allowed singers to redirect their focus toward healthy vocal technique and ensemble unity, fostering improved expression, phrasing, and overall musicality. Completing graduate studies in music at Kansas State University has been a transformative experience. The practical courses, most notably Advanced Choral Rehearsal Techniques, provided rich opportunities for collaboration and experimentation with colleagues and professors as we explored innovative approaches to teaching music through performance in choir. Implementing creative warm-ups, musically responsive gestures, and pedagogical insights has transformed my choral rehearsals into dynamic, engaging music-making experiences. It has been deeply fulfilling to synthesize my passion for sacred music, particularly Gregorian chant, with these practical innovations to meet the unique needs of my students and school community. The most rewarding aspect of the program has certainly been the didactic courses, especially History and Philosophy of Music Education and Theories of Music Teaching, which challenged me to reflect on my core values as an educator. Each course inspired a renewed commitment to professional development, a deepened engagement with current literature in music education, and a stronger drive to offer the highest quality instruction to my students. Ultimately, this journey has empowered me to more intentionally use Gregorian chant not only as a meaningful expression of faith, but also as a powerful, research-informed tool for cultivating ensemble skills and musical excellence.
Keywords: Choral music education; Sacred music; Gregorian chant; Vocal pedagogy; Catholic classical education; Rehearsal techniques